Assessment of Geodiversity Values of Banyu Anjlok, Malang Regency, as a Potential Geological Heritage - Faris, Ahmad Najmi; Adi Susilo; Alexander Tunggul Sutan Haji; Izza Safira (Tinta Emas Publisher, 2024)
Banyu Ajlok is one of the tourist destinations in Purwodadi Village, Tirtuyudo District, Malang Regency. Banyu Anjlok is located in the southern mountainous area, this area shows the existence of ancient volcanic activity from the south of Java which causes Banyu to have a geodiversity that can be used as a geological heritage. The purpose of this study is to identify geodiversity in the Banyu plummeting area as the basis for geological-based tourism development. The methods used include geological surveys and assessments of geological values using the technical guidelines of the Geological Survey Center by the Geological Survey Center which include scientific values, educational values, tourism values and risk of degradation. The results showed that the lithology of Banyu plummeted including andesite, basalt, ryolite, andesite breccia, sandstone, grandiorit and plant fossils. In addition, geological structures that can be found are joints. The assessment results show a scientific value of 76.25%, an educational value of 75%, a tourism value of 66.25% and a risk of degradation of 235. Based on the results of the assessment, Banyu plummeting has potential as a geological heritage site in terms of geological diversity and risk of degradation.